PARTISIPASI MASYARAKAT DESA DALAM PELAKSANAAN PEMBANGUNAN DI DESA PUSEURJAYA KECAMATAN TELUKJAMBE TIMUR KABUPATEN KARAWANG - Irfan Rizki Fauzi; Usep Dayat; Mochamad Faizal Rizki (Jurnal Intervensi Sosial dan Pembangunan, 2023)
Development is something that is important for a region and a country though. The purpose of development itself is to improve the welfare of the community. Therefore, development is carried out continuously as a process in order to achieve a better state of society. Development milestones come from the most basic level of government, namely the village, the village has the right to run and develop its own area according to the competence of each region. As for village development, there are many parties who participate in the implementation of village development, one of which is the participation of the village community. However, in its implementation, community participation is considered less active in contributing. This may be the case in Puseur Jaya Village, where most of the villagers work as employees who do not have much time to participate in the implementation of development. The method used in this research is descriptive analytical with qualitative research type. The results of this study explain that there are two forms of village community participation in the implementation of village development, namely by being physically present and secondly contributing ideas and ideas for the implementation of village development. Keywords: Village, Community, Participation, Development